Development of a European Public Health Emergency Preparedness Training Toolkit. (13th November 2019) - Guicciardi, S; Fantini, M P; Savoia, E; Stoto, M A; Nelson, C; Piltch-Loeb, R; Pommier, J; Ciotti, M; Riley, P
Abstract: Background: In 2017, under the supervision of the European Centre for Disease Prevention and Control (ECDC), a list of competencies and knowledge and skill statements for EU professionals working in Public Health Emergency Preparedness (PHEP) systems were identified and integrated into a Competency Model. Building on these efforts, a PHEP competency-based training toolkit was developed, pilot tested and finalized with the goal of providing a standardized training resource for experts involved in response to cross-border threats to health. Objectives: Led by the ECDC, an international research team drafted a preliminary version of a curriculum consisting of five modules, with a list of targeted competencies, learning objectives, reading and training methods including case studies and simulation exercises. In May 2018, the curriculum was pilot tested in a 3.5-day training course at the University of Bologna, Italy. The participants included 20 representatives from 8 EU Member States. An evaluation strategy, combining both quantitative and qualitative methods, was designed to assess the impact of the training on participants' applied knowledge and competence. Results: Overall, the participants' feedback on the pilot course was positive, with scores from 4.0 to 4.8 out of 5 for all the items considered. Several suggestions were made both by the trainers and the trainees to enhance the effectiveness of the learning activities, and the curriculum was integrated into a training toolkit with more exercises, teaching materials and a guide for facilitators. Conclusions: This European Public Health Emergency Preparedness Training Toolkit is the first EU competency-based toolkit intended to help Member States improve their response to public health emergencies through standardized training. Designed for individuals working in strategic positions at the national level, its general approach, modular structure and content are relevant and can be tailored to a wider range of professionals. Key messages: To improve PHEP in the EU, competency-based curricula and standardized training programs and resources for health professionals are needed. By enhancing the overall public health professionals' experience and competency, the European PHEP Training Toolkit represents a step towards strengthening preparedness and response systems in the EU.